شخصيّة المرأة والالتزام الإسلاميّ في رواية "عذراء جاكرتا" لنجيب الكيلاني / Islamic commitment of female characters in 'Jakarta's Virgin' by Najib al-Kilani - Ismail, Taufik; Ahmad, Muhammad Anwar; Haeruddin, Ilham Ramadhan; Salleh, Abdul Halim; Nasir, Mohd Shahrizal (IIUM Press, 2022)
يدرس هذا البحثُ شخصيّات المرأة في رواية "عذراء جاكرتا" لنجيب الكيلاني من منظور النقد الروائي ومنهج الأدب الإسلاميّ، ويهدف البحث إلى إبراز أبعاد شخصية المرأة في الرواية وطرق تصويرها ورسمها ومدى التزامها الإسلاميّ. ويتبنّى البحث منهج تحليل المحتوى المتمثل في تحليل نصوص رواية "عذراء جاكرتا" المتعلقة بشخصيات المرأة مركزا على أبعاد الشخصيّات وطرق تصويرها ورسمها. وتكمن أهمية البحث في عنايته بالرواية الإسلاميّة الملتزمة، إضافة إلى الاهتمام بشخصية المرأة من منظور الأدب الإسلاميّ ومكانة المرأة وأهميتها في النتاج الروائيّ الإسلاميّ. وقد تم اختيار رواية "عذراء جاكرتا" نموذجا للدراسة لتناولها شخصيّات المرأة المتنوعة فضلا عن علاجها للصراعات التي تتعلق بالمرأة. وقد توصّل البحث إلى أن رواية "عذراء جاكرتا" رواية إسلاميّة ملتزمة وأن كاتبها قد نجح في تصوير شخصيّات المرأة وفقا للرؤية الإسلاميّة، كما أثبت إبداعيّته الروائيّة. / This study examines the female characters in Jakarta’s Virgin by Najib al-Kilani of Egypt from the perspective of literary criticism and Islamic literature. This research analyses the dimensions of the female characters and the writer’s methods of characterization as well as the Islamic values in the novel. The research adopts the content analysis method by analyzing the texts of the novel Jakarta’s Virgin related to the women characters, focusing on the dimensions of the characters and the ways of portraying them. The significant of the research lies in its interest in the committed Islamic novel, in addition to the interest in the personality of women from the perspective of Islamic literature and the status and importance of women in the production of Islamic novels. The novel Jakarta’s Virgin was chosen as a model for the study because it deals with the various women characters, as well as its treatment of conflicts related to women. The research concluded that the novel Jakarta’s Virgin is a committed Islamic novel and that its writer succeeded in portraying the women characters according to the Islamic view, as he proved his novelistic creativity.